Late Effects of Cancer Treatment, Job Resources, and Burnout Complaints Among Employees With a Breast Cancer Diagnosis 2–10 Years Ago: A Longitudinal Study - Boelhouwer, Ingrid G.; Vermeer, Willemijn; van Vuuren, Tinka (Frontiers in Psychology, 2022)
Purpose The aim of this study was to investigate the effect of possible late effects of cancer treatment (physical complaints, fatigue, and cognitive complaints) and of two job resources (autonomy and supportive leadership style) on future burnout complaints, among employees living 2–10 years beyond breast cancer diagnosis. Methods Data at T1 (baseline questionnaire) and at T2 (9 months later) were collected in 2018 and 2019 (N = 287). These data were part of a longitudinal study among Dutch speaking workers with a cancer diagnosis 2–10 years ago. All complaints and job resources were self-reported. Longitudinal multivariate regression analyses were executed, controlling for years since diagnosis, living with cancer (recurrence or metastasis), and other chronic or severe diseases. Mediation by baseline burnout complaints was considered. Results A higher level of fatigue and cognitive complaints at baseline (T1) resulted in higher future burnout complaints (at T2), with partial mediation by baseline burnout complaints. No effect of physical complaints at T1 was observed. Higher levels of autonomy or a supportive leadership style resulted in lower burnout complaints, with full mediation by baseline burnout complaints. Buffering was observed by autonomy in the relationship of cognitive complaints with future burnout complaints. No moderation was observed by supportive leadership. Conclusion The level of burnout complaints among employees 2–10 years beyond breast cancer diagnosis may be an effect of fatigue or cognitive complaints, and awareness of this effect is necessary. Interventions to stimulate supportive leadership and autonomy are advisable, the latter especially in the case of cognitive complaints.